Perceived characteristics of innovation (PCI) model - Razali, Ummi Syahira; Mansor, Yushiana (IIUM Press, 2011)
This chapter introduces the Perceived Characteristics of Innovation (PCI) model. It explores previous literature that has employed the PCI model in various researches in ICT